Integration of Genomics in Cancer Care - Santos, Erika Maria Monteiro; Edwards, Quannetta T.; Floria-Santos, Milena; Rogatto, Silvia Regina [UNESP]; Achatz, Maria Isabel Waddington; MacDonald, Deborah J. (Wiley, 2013)
Purpose: The article aims to introduce nurses to how genetics-genomics is currently integrated into cancer care from prevention to treatment and influencing oncology nursing practice. Organizing Construct: An overview of genetics-genomics is described as it relates to cancer etiology, hereditary cancer syndromes, epigenetics factors, and management of care considerations. Methods: Peer-reviewed literature and expert professional guidelines were reviewed to address concepts of genetics-genomics in cancer care. Findings: Cancer is now known to be heterogeneous at the molecular level, with genetic and genomic factors underlying the etiology of all cancers. Understanding how these factors contribute to the development and treatment of both sporadic and hereditary cancers is important in cancer risk assessment, prevention, diagnosis, treatment, and long-term management and surveillance. Conclusions: Rapidly developing advances in genetics-genomics are changing all aspects of cancer care, with implications for nursing practice. Clinical Relevance: Nurses can educate cancer patients and their families about genetic-genomic advances and advocate for use of evidence-based genetic-genomic practice guidelines to reduce cancer risk and improve outcomes in cancer management. © 2013 Sigma Theta Tau International.
Keywords: Cancer; Genetics; Genomics; Risk assessment